The National Eye Survey of Trinidad and Tobago (NESTT): Rationale, Objectives and Methodology. (4th March 2017) - Braithwaite, Tasanee; Verlander, Neville Q.; Bartholomew, Debra; Bridgemohan, Petra; McNally, Kevin; Roach, Allana; Sharma, Subash; Singh, Deo; Pesudovs, Konrad; Teelucksingh, Surujpal; Carrington, Christine; Ramsewak, Samuel; et al.
ABSTRACT: Purpose : This paper describes the rationale, study design and procedures of the National Eye Survey of Trinidad and Tobago (NESTT). The main objective of this survey is to obtain prevalence estimates of vision impairment and blindness for planning and policy development. Methods : A population-based, cross-sectional survey was undertaken using random multistage cluster sampling, with probability-proportionate-to-size methods. Eligible participants aged 5 years and older were sampled from the non-institutional population in each of 120 cluster segments. Presenting distance and near visual acuity were screened in their communities. People aged 40 years and older, and selected younger people, were invited for comprehensive clinic assessment. The interview included information on potential risk factors for vision loss, associated costs and quality of life. The examination included measurement of anthropometrics, blood glucose, refraction, ocular biometry, corneal hysteresis, and detailed assessment of the anterior and posterior segments, with photography and optical coherence tomography imaging. Adult participants were invited to donate saliva samples for DNA extraction and storage. Results : The fieldwork was conducted over 13 months in 2013–2014. A representative sample of 10, 651 individuals in 3410 households within 120 cluster segments identified 9913 people who were eligible for recruitment. Conclusion : The study methodology was robust and adequate to provide the first population-based estimates of the prevalence and causes of visual impairment and blindness in Trinidad and Tobago. Information was also gathered on risk factors, costs and quality of life associated with vision loss, and on normal ocular parameters for the population aged 40 years and older.